استدراكات يحيى بن حمزة (749هـ) النحوية على ابن بابشاذ (469هـ) في كتابه (الحاصر لفوائد مقدمة طاهر في علم حقائق الإعراب/ Yahya ibn Hamzah’s (d. 749 AH) Syntactic Annotations in Ibn Babshādh (d. 469AH): A Study Based on His Work (Al-Ḥāṣir li-Fawāʾid Muqadd - O. H. Rannah, Muhannad (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2025)
ملخص البحث: بدأت الكتب التعليمية بالظهور منذ القرن الرابع الهجري، وامتازت عما سبقها بالإيجاز ووضوح الشواهد والشمول، وقد أثارت هذه الكتب حركة علمية؛ إما عبر تدريسها أو عبر شرحها؛ لتقريبها من أذهان المتعلمين نظراً إلى إيجازها، ومنها كتاب المقدمة المحسبة لابن بابشاذ الذي اشتهر وكثرت شروحه، يسعى البحث إلى تسليط الضوء على استدراكات يحيى بن حمزة على ابن بابشاذ في شرحه لكتاب المقدمة المحسبة المسمَّى الحاصر لفوائد مقدمة طاهر في علم حقائق الإعراب، عبر منهج وصفيٍّ تحليليٍّ، يكشف عن أبرز الاستدراكات التي وقف عليها يحيى بن حمزة وبيان موقفه من آراء ابن بابشاذ، وقد خلص البحث إلى أن يحيى بن حمزة اتسم في استدراكاته بالاعتدال والنظرة الموضوعية، وإلى تعدُّد أغراض استدراكاته ما بين التصحيح والإكمال والإشارة إلى قول أو معنى أولي. الكلمات المفتاحية: استدراك، ابن بابشاذ، المقدمة، المحسبة، يحيى بن حمزة. Abstract: Didactic grammatical literature began to flourish in the fourth century AH (tenth century CE), distinguishing itself from earlier works through its conciseness, clarity of illustrative examples, and comprehensive scope. These characteristics contributed to a surge in scholarly engagement, as such texts were either taught directly or elucidated through detailed commentaries aimed at bridging the gap between brevity and comprehension for students. Among the most prominent of these instructional works is al-Muqaddimah al-Muḥsabiyyah by Ibn Bābshādh, a widely studied text that attracted numerous commentaries. This study investigates the emendations made by Yahya ibn Hamzah to Ibn Bābshādh’s grammatical positions, as presented in his commentary entitled al-Ḥāṣir li-Fawāʾid Muqaddimat Ṭāhir fī ʿIlm Ḥaqāʾiq al-Iʿrāb. Utilizing a descriptive and analytical approach, the research identifies the principal points of critique and explores Yahya ibn Hamzah’s evaluative stance on the views advanced by Ibn Bābshādh. The findings reveal that Yahya’s approach to criticism is marked by intellectual moderation and methodological objectivity. Furthermore, the study demonstrates the multifaceted purposes of his emendations, which range from correction and supplementation to the preference for alternative interpretations and reasoned rebuttals. Keywords: Critical emendation; Ibn Bābshādh; al-Muqaddimah al-Muḥsabiyyah; Yahya ibn Hamzah; Arabic grammar. Abstrak: Penulisan buku pengajaran tatabahasa Arab mula berkembang sejak abad keempat Hijrah dan mula menampakkan keunikan berbanding penulisan sebelumnya dari segi gaya penyampaian yang ringkas, contoh yang jelas serta liputan isi kandungan yang menyeluruh. Buku-buku ini telah mencetuskan anjakan paradigma melalui pengajaran buku-buku tersebut secara langsung mahupun penulisan syarah sebagai usaha untuk menjelaskan isi kandungannya yang bersifat ringkas kepada para pelajar. Salah satu karya penting dalam konteks ini ialah al-Muqaddimah al-Muhsibah oleh Ibn Babshadz, yang masyhur dan banyak dihuraikan. Kajian ini bertujuan menyoroti penambahbaikan (istidrak) yang dilakukan oleh Yahya bin Hamzah terhadap Ibn Babshadz dalam al-Muqaddimah al-Muhsibah melalui syarahnya yang berjudul al-Hasir li Fawa'id Muqaddimat Tahir fi 'Ilm Haqa'iq al-I'rab. Kajian ini menggunakan pendekatan deskriptif-analitik untuk mendedahkan bentuk-bentuk istidrak yang dikemukakan oleh Yahya bin Hamzah terhadap pandangan Ibn Babshadz, serta menjelaskan pendiriannya terhadap isu-isu yang dibincangkan. Hasil kajian menunjukkan bahawa Yahya bin Hamzah bersikap sederhana dan objektif dalam penambahbaikan yang dilakukannya. Tujuan istidrak beliau berbeza-beza, antaranya membetulkan apa yang tersilap, melengkapan apa yang kurang, menyebut pandangan lain, serta cadangan terhadap pandangan yang lebih tepat atau sesuai. Kata kunci: Istidrak, Ibn Babshadz, al-Muqaddimah, al-Muhsibah, Yahya bin Hamzah.